2018
DOI: 10.1257/aer.20160133
|View full text |Cite
|
Sign up to set email alerts
|

How Does Household Income Affect Child Personality Traits and Behaviors?

Abstract: We examine the effects of a quasi-experimental unconditional household income transfer on child emotional and behavioral health and personality traits. Using longitudinal data, we find that there are large beneficial effects on children’s emotional and behavioral health and personality traits during adolescence. We find evidence that these effects are most pronounced for children who start out with the lowest initial endowments. The income intervention also results in improvements in parental relationships whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(57 citation statements)
references
References 81 publications
1
49
0
1
Order By: Relevance
“…Our monitoring component shares elements of the parental monitoring index developed by Small and Kerns (1993) and has similarities with Baumrind's (1973) parental control dimension of parenting style. Closely-related constructs have also been identified in the recent literature in economics (Ermisch, 2008;Fiorini & Keane, 2014;Akee et al 2015). …”
Section: Tablementioning
confidence: 93%
“…Our monitoring component shares elements of the parental monitoring index developed by Small and Kerns (1993) and has similarities with Baumrind's (1973) parental control dimension of parenting style. Closely-related constructs have also been identified in the recent literature in economics (Ermisch, 2008;Fiorini & Keane, 2014;Akee et al 2015). …”
Section: Tablementioning
confidence: 93%
“…There have been a handful of longitudinal studies testing the effect of stress during childhood and social behavior in adulthood using exogenous shocks of positive or negative income shocks on different behavioral outcomes. These studies have shown that higher levels of income tend to make individuals more 'agreeable' and more trustful (Akee et al, 2018;Hörl et al, 2016) while higher levels of violence during childhood make people more antisocial and more violent (Gangadharan et al, 2017;Miguel et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…One of the most noteworthy pieces of research in this area is a quasi-experimental study led Akee et al (2018). In this study, American Indian children were exposed to a positive income shock following the opening of a casino that decided to allocate part of its revenue to Cherokee households.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Less is known about the impact of income on children. One study found that an increase in income amongst families in poverty is associated with emotional and behavioral benefits for children [32]. However, because it is often not practical to supplement family income directly, a more tractable goal may be to support parental socioeconomic mobility [33,34].…”
Section: Improving Cognitive Skills: Lessons From Visual Neurosciencementioning
confidence: 99%